An Orthognathıc Approach To Facıal Asymmery - Neslihan Üçüncü; Orhan Güven (Galenos Yayinevi, 1990)
Facial asymmetry which occurs as a result of different effects, may be seen at diffierent parts of the face. The jaws are frequently the cause of facial asymmetry. Especially, the mandible is a major contributor to facial asymmetry. In this paper, the technique of genioplasti was applied to a patient who had mandibular asymmetry. Differences between preoperatif and postoperatif cephalometric values has been discussed.